2015
DOI: 10.1007/s10120-015-0478-z
|View full text |Cite
|
Sign up to set email alerts
|

TSPAN8, identified by Escherichia coli ampicillin secretion trap, is associated with cell growth and invasion in gastric cancer

Abstract: Background Gastric cancer (GC) is one of the most common human cancers. Genes expressed only in cancer tissue, especially on the cell membrane, will be useful biomarkers for cancer diagnosis and therapeutics. Methods To identify novel genes encoding transmembrane protein specifically expressed in GC, we generated an Escherichia coli ampicillin secretion trap (CAST) library from diffuse-type GC cell line MKN-45. CAST is a survival-based signal sequence trap method that exploits the ability of mammalian signal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…The bioinformatics analysis showed that the potential binding sites of miR‐324‐5p presented in the 3′‐UTR of Tetraspanin 8 (TSPAN8), suggesting the possible interaction between miR‐324‐5p and TSPAN8. More importantly, TSPAN8 was confirmed to induce cell growth and invasion in gastric cancer . So, the purpose of this study was to explore whether miR‐324‐5p was involved in gastric cancer via regulating TSPAN8.…”
Section: Introductionmentioning
confidence: 99%
“…The bioinformatics analysis showed that the potential binding sites of miR‐324‐5p presented in the 3′‐UTR of Tetraspanin 8 (TSPAN8), suggesting the possible interaction between miR‐324‐5p and TSPAN8. More importantly, TSPAN8 was confirmed to induce cell growth and invasion in gastric cancer . So, the purpose of this study was to explore whether miR‐324‐5p was involved in gastric cancer via regulating TSPAN8.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent study of Escherichia coli ampicillin secretion trap (CAST) analysis on GC cell lines and cancer tissues identified several candidate genes. Desmocollin 2 (DSC2) expression was associated with GC of the intestinal mucin phenotype with CDX2 expression [15] and transmembrane 9 superfamily member 3 (TM9SF3) expression was significantly associated with tumor progression and involved in cancer cell invasion [16]. These results indicated the methods to be useful for the identification of novel genes associated with GC; however, such alterations cannot completely explain the pathogenesis of GC.…”
Section: Introductionmentioning
confidence: 99%
“…We previously generated CAST libraries from two GC cell line CAST libraries-MKN-1 [15], and MKN-45 [16]and normal stomach [15]. CAST is a useful method for identifying novel biomarkers and new therapeutic targets.…”
Section: Fktn Overexpression In Gc Cell Line Cast Librariesmentioning
confidence: 99%
“…In cancer and immunity studies, TSPAN8 has been intensively studied and found to regulate various cellular process such as cell migration, proliferation and differentiation. (Minami et al;Livak and Schmittgen, 2001;Bustin et al, 2009;Anami et al) . Furthermore, TSPAN8 has been shown to be widely expressed in various tissue types (Pan et al) , which is consist with our findings and further speaks to its diverse functions.…”
Section: Discussionmentioning
confidence: 98%